The Influence of Professional Socialization, Financial Rewards, and Job Market Capacity on The Interest in Becoming an Auditor With Self-Competence as a Moderating Variable - Malakani, Rizma; Tenriwaru, Tenriwaru; Ramdani, Muh Reza (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2024)
Purpose - This study aims to examine the Influence of Professional Socialization, Financial Rewards, and Labor Market Capacity on Interest in Becoming an Auditor with Self-Competence as a Moderating Variable Design/methodology/approach – The research employs a quantitative method using questionnaires with a population of 157 individuals. The sample of 61 respondents was selected through random sampling. The research analysis utilizes multiple regression analysis conducted with SPSS software Findings – The results indicate that professional socialization does not have a positive and significant influence on interest in becoming an auditor. Financial rewards have a positive and significant influence on interest in becoming an auditor, while labor market capacity also demonstrates a positive and significant influence on interest in becoming an auditor. Additionally, self-competence moderates the influence of financial rewards and labor market capacity on interest in becoming an auditor Originality – This research used questionnaires with a population of 157 people, and the sample was selected using random sampling, resulting in 61 individuals being chosen as the sample Keywords: Professional Socialization, Financial Rewards, Labor Market Capacity, Interest in Becoming an Auditor, Self-Competence Paper type Research Result